2017
DOI: 10.1038/onc.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-mediated activation of LDHA promotes cancer cell invasion and tumour metastasis

Abstract: Metastases remain the major cause of death from cancer. Recent molecular advances have highlighted the importance of metabolic alterations in cancer cells, including the Warburg effect that describes an increased glycolysis in cancer cells. However, how this altered metabolism contributes to tumour metastasis remains elusive. Here, we report that phosphorylation-induced activation of lactate dehydrogenase A (LDHA), an enzyme that catalyses the interconversion of pyruvate and lactate, promotes cancer cell invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(162 citation statements)
references
References 50 publications
3
158
1
Order By: Relevance
“…Lactate dehydrogenase has 2 subunits that contained an enzyme that catalyzes the interconversion between pyruvate and lactate, and LDHA is mostly responsible for anaerobic and pyruvate metabolism. Up-regulation of PDK4 or LDHA ensures efficient glycolysis for tumor cells, which is believed to play an important role in anoikis resistance, invasion, and metastasis in human cancer (47)(48)(49). Similarly, increased expression of PDK4 and LDHA has also been confirmed in PCa and might be associated with tumor progression (50,51).…”
Section: Discussionmentioning
confidence: 97%
“…Lactate dehydrogenase has 2 subunits that contained an enzyme that catalyzes the interconversion between pyruvate and lactate, and LDHA is mostly responsible for anaerobic and pyruvate metabolism. Up-regulation of PDK4 or LDHA ensures efficient glycolysis for tumor cells, which is believed to play an important role in anoikis resistance, invasion, and metastasis in human cancer (47)(48)(49). Similarly, increased expression of PDK4 and LDHA has also been confirmed in PCa and might be associated with tumor progression (50,51).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover it has been reported that it promotes cancer cell invasion, anoikis resistance and tumor metastasis, via HER2 and Src pathways [43,44]. It has also been demonstrated that an experimentally increased expression of 14-3-3ζ in human mammary epithelial cells up-regulates LDHA expression, elevates glycolytic activity, and promotes early transformation through the MEK-ERK-CREB axis [45].…”
Section: L-lactate Dehydrogenase a Chain Ldha (Ldha)mentioning
confidence: 99%
“…Phosphorylation significantly increased enzymatic activity of LDHA, which is associated with cancer progression. In breast cancer, Jin et al revealed that Y10 phosphorylation elicited LDHA activation, promoting cancer cell invasion and enhancing anoikis resistance. Also in colorectal cancer, Ji et al found that human coilin–interacting nuclear ATPase protein (hCINAP) expression was positively correlated with the level of Y10 phosphorylated LDHA.…”
Section: Regulation Modes Of Ldhamentioning
confidence: 99%